Analisis Kesulitan Membaca Pemahaman Siswa Kelas IV Sekolah Dasar Sulit Air - Fadhilla, Nurul; Putri L., Sabrina Novita; Chandra, Chandra; Wijanarko, Tiok (TSAQOFAH, 2024)
The aim of this study is to describe the reading comprehension difficulties of fourth-grade students at Sulit Air Elementary School in learning the Indonesian language. This study employs a qualitative research design with a descriptive method. The subjects of this study are fourth-grade students who still experience difficulties in reading comprehension. The data analyzed were obtained through observation, interviews, and documentation. In terms of literacy, the comprehension of elementary students who struggle is still considered low. The results of the study indicate that there are two students who still have difficulties in understanding readings. The students cannot answer sentences or questions correctly but repeat them in simple sentences. Students can answer questions but not optimally. The ability to explain the meaning of difficult words in the reading is very low and not yet optimal. The teacher's effort to overcome students' reading comprehension difficulties is by applying the SQ3R method (Survey, Question, Read, Recite, Review).